Environmental risk assessment of Pb, Cu, Zn, and Cd concentrations accumulated in selected mangrove roots and surrounding their sediment - ROZIRWAN ROZIRWAN; NADILA NUR KHOTIMAH; WIKE AYU EKA PUTRI; FAUZIYAH FAUZIYAH; RIRIS ARYAWATI; NURHAYATI DAMIRI; ISNAINI ISNAINI; REDHO YOGA NUGROHO (Society for Indonesian Biodiversity, 2023)
Abstract. Rozirwan, Khotimah NN, Putri WAE, Fauziyah, Aryawati R, Damiri N, Isnaini, Nugroho RY. 2023. Environmental risk assessment of Pb, Cu, Zn, and Cd concentrations accumulated in selected mangrove roots and surrounding their sediment. Biodiversitas 24: 6733-6742. Mangroves as the largest coastal ecosystem can accumulate heavy metals from their environment. This study aimed to evaluate the environmental risk associated with heavy metal pollution accumulated in the roots of mangroves and the surrounding sediments. The mangrove roots consisted of three species Sonneratia caseolaris, Rhizopora apiculata, and Xylocarpus granatum, collected from three observation stations within the Payung Island mangrove ecosystem in South Sumatra, Indonesia. The concentrations of heavy metals were determined using atomic absorption spectrometry. Statistical analysis employed one-way Analysis of Variance (ANOVA). At the same time, ecological risk assessment utilized the Bioconcentration Factor (BCF), Geoaccumulation Index (Igeo), Contamination factor (Cf), and Pollution Load Index (PLI). The highest sediment concentrations of heavy metals at station 3 were 12.786±0.26 mg/kg for Pb, 10.413±0.011 mg/kg for Cu, 42.752±0.053 mg/kg for Zn, and Cd was not detected. In mangrove roots, the highest concentrations were found in S. caseolaris, with 2.596±0.002 mg/kg for Pb and 11.881±0.015 mg/kg for Zn, while X. granatum exhibited 8.850±0.011 mg/kg for Cu and 0.160±0.020 mg/kg for Cd. BCF values <1 were categorized as exclusion, Igeo<0 indicated non-contamination, Cf<1 signified low pollution, and PLI<0 denoted an unpolluted status. Based on the results, the quality of the mangrove ecosystems affected by heavy metal pollution is currently considered safe regarding environmental risk assessment.